Development of the firmware for healthcare device using smart devices - Chua, Huai Chee (2014)
The author realized the problem of shortage of nurses is getting serious. The workloads of doctors and nurses are getting heavier and heavier. In this situation, the author came out an idea and solution and proposed to solve these problems. The author would like to develop the firmware for the smart healthcare device system. The author develops the mobile apps and pc apps as user interface. For the function of the system, the author develops a database, voice recognition function, detection falling down function and indoor localization system. The software/languages which the author integrated with are Visual Studio 2013(VB), Visio, MySQL, PHP and Android programming. The hardware which the author integrated with are Arduino, RFID, gyrometer, accelerometer and etc.